Definiteness in Superlatives - Krasikova, Sveta (Proceedings of the Amsterdam Colloquium, 2011)
A new analysis of superlatives is presented, which assigns two functions to the definite article. It reflects the definiteness of the DP in absolute superlatives, and the definiteness of the DegP in comparative superlatives. The analysis accounts for the distribution of the in attributive, amount, predicative and adverbial superlatives in English.